Comment on "Judgment, truth and reality in F. H. Bradley" - Miranda Rojas, Rafael (2024)
Commented article: Briceño, Sebastián. Juicio, verdad y realidad en F. H. Bradley. Trans/Form/Ação: Revista de Filosofia da Unesp, v. 47, n. 3, e02400217. Avaliable on: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15708.